Potential of Horticultural Farming and Factors Affecting Production in Mbeere North Sub County - Mulwa, Ann (University of Embu, 2019)
For over four years, the residents of Mbeere North Sub County used to survive on relief food, and majority of them had to work as casual laborers in order to earn a living for the basic human needs. However, with some of the initiatives such as irrigation project initiated by Trocaire in collaboration with Ishiara Catholic Parish many people have drastically adopted horticultural farming using the irrigation scheme and many more projects although they still face numerous shortcoming in horticultural farming. This study aimed at identifying various socio-economic variables that affect horticultural farmers in Mbeere North Sub County. It targets to identify the potential of horticultural farming in the area of study. The study was divided into five clusters and the clusters shall represent locations using households as sampling units: Five households were selected per cluster using simple random sampling techniques. A total of two hundred respondents were interviewed using structural questionnaires. In each location, four sub-locations were identified and twenty households from each sub-location were interviewed using simple technique random of sampling design. The data collected was processed and analyzed using the Statistical Package for Social Sciences (SPSS) and presented in the form of tables, graphs and frequencies. The study showed that government incentives such as provision of irrigation facilities, farm inputs and agricultural extension can play a major role in ensuring that the full potential of horticultural farming in Mbeere North Sub County is realized.